Evaluation of two methods for monitoring the blackmargined pecan aphid and its predators - Boscardin, Jardel; Costa, Ervandil Corrêa (EntomoBrasilis, 2024)
The present study aimed to evaluate, qualitatively and quantitatively, yellow sticky traps and entomological net in the monitoring of Monellia caryella (Fitch, 1855) (Hemiptera: Aphididae) and its predators in a pecan plantation in Santa Maria, Rio Grande do Sul, Brazil. This plantation was implemented on 1.2 ha in February 2012 with the Barton and Shawnee varieties at a spacing of 7 m x 7 m. Twenty pecan plants were randomly selected to sample the blackmargined pecan aphid and its predators. From November 2014 to May 2015, 13 collections were carried out with yellow sticky traps and an entomological net. A total of 898 arthropod specimens were collected, 50.9% of which were from yellow sticky traps and 49.1% from the entomological net trap. Regarding the yellow sticky traps, only M. caryella was identified at the species level, with the predators identified at the taxonomic levels of order (Araneae) and family (Coccinellidae; Coleoptera). In terms of the entomological net, all the insects of interest at the species level were identified. There was a significant difference only between the averages in the number of Araneae specimens, with the highest density found in the yellow sticky traps. Both methods provided the correct identification of M. caryella and efficiently recorded its population peak. It is concluded that yellow sticky traps are effective for monitoring M. caryella, while the entomological net is suitable for monitoring and correctly identifying species of natural enemies of the insect pest in pecan plantations.